ASPIRASI REFORMASI HUKUM DAN PENEGAKAN HUKUM PROGRESIF MELALUI MEDIA HAKIM PERDAMAIAN DESA - Tedi Sudrajat (Jurnal Dinamika Hukum, 2010)
Strategies of law enforcement are functioned to reduce the social conflicts that represent the aspiration of legal reform at local level, which the output is to support the government of Indonesia in establishing the accommodative legal system. In Indonesian social life, the values ought to be explored through the village as the lowest governmental organizations and the closest area with the society. These functions can create the village as a strategic area to create the justice at local level, and therefore the role of village judge required the village as a place that can accommodate the interests of the society. Keywords: law enforcement, law reform, village judge